Prevalence and influencing factors of suicide in first-episode and drug-naive young major depressive disorder patients with impaired fasting glucose: a cross-sectional study - Li, Yifan; Liao, Zhenjiang; Huang, Qiuping; Wang, Qianjin; Ren, Honghong; Chen, Xinxin; Lin, Shuhong; Wang, Chenhan; Tang, Ying; Hao, Jingyue; Wang, Xuhao; Shen, Hongxian; et al. (Frontiers in Psychiatry, 2023)
Background: An association exists between major depression disorder (MDD), suicide attempts, and glucose metabolism, but suicide attempts in young MDD patients with comorbid impaired fasting glucose (IFG) have been less well studied. The purpose of this study was to examine the prevalence and risk factors for suicide attempts in young, first-episode, drug-naive (FEDN) MDD patients with comorbid IFG. Methods: We recruited 917 young patients with FEDN MDD, 116 of whom were judged to have combined IFG because their blood glucose was >6.0. We collected anthropological and clinical data on all of them. The Hamilton Depression Scale (HAMD) score, the Hamilton Anxiety Scale (HAMA) score and the Positive and Negative Syndrome Scale (PANSS) positive subscale score were used to assess their clinical symptoms. Blood glucose, plasma thyroid function and lipid indicators were measured. Results: The prevalence of suicide attempts in young MDD patients with IFG was 32.8% (38/116). Furthermore, among young MDD patients with comorbid IFG, suicide attempters had more severe depression and anxiety symptoms, more comorbid psychotic symptom, higher levels of antibody of thyroid stimulating hormone and thyroid peroxidases (TPOAb), and more severe lipid metabolism disorders than those without suicide attempts. In addition, HAMA scores and TPOAb were independently associated with suicide attempts in young patients with FEDN MDD. Conclusion: Our study suggests that young MDD patients with IFG have a high rate of suicide attempts. Some clinical symptoms and thyroid function parameters may be the risk factor for suicide attempts in young MDD patients with impaired glucose metabolism.